2020
DOI: 10.3390/cancers12113337
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Color Deconvolution and Color Normalization for Automated Classification of Histology Images Stained with Hematoxylin and Eosin

Abstract: Histological evaluation plays a major role in cancer diagnosis and treatment. The appearance of H&E-stained images can vary significantly as a consequence of differences in several factors, such as reagents, staining conditions, preparation procedure and image acquisition system. Such potential sources of noise can all have negative effects on computer-assisted classification. To minimize such artefacts and their potentially negative effects several color pre-processing methods have been proposed in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…We estimated that our lymphocyte classifier would perform better in cell detection and classification after color normalization possibly as it was developed with a random trees algorithm. However, convolutional neural network-based image analysis could improve classification due to lower sensitivity for technical color variations [ 41 ]. Moreover, we found immune excluded tumors to associate with fewer metastatic organs and superior overall survival in our primary dataset, representing a potential clinical biomarker in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated that our lymphocyte classifier would perform better in cell detection and classification after color normalization possibly as it was developed with a random trees algorithm. However, convolutional neural network-based image analysis could improve classification due to lower sensitivity for technical color variations [ 41 ]. Moreover, we found immune excluded tumors to associate with fewer metastatic organs and superior overall survival in our primary dataset, representing a potential clinical biomarker in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the black and white images could be a source of interobserver variability, but we assume that they might be better suited for reproducible deep learning analyses between different centers by avoiding the considerable differences in H&E staining results of different laboratories [ 42 ]. Up to now, no standardized staining platform for H&E has received wide acceptance, and in most cases color pre-processing does not improve classification accuracy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others investigated only one or two methods or a limited number of images and datasets, and therefore lack generalizable conclusions [18,23,27,29,33,35,36]. Recently, Bianconi et al [37] compared multiple methods on various cancer types but only reported the classification efficacy on microscopic regions of sections (e.g. 256 Â 256 pixels; referred to as patches) sampled from WSIs, as opposed to slide-level results which would be translatable and applicable to patient diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…256 Â 256 pixels; referred to as patches) sampled from WSIs, as opposed to slide-level results which would be translatable and applicable to patient diagnosis. Furthermore, the effect of color normalization for classifier performance is primarily studied in the context of images in which both training and testing sets originate from one center, such as a single hospital or research institute [23,26,34,35,37]. Single-center color inconsistencies between WSIs are mainly due to sample processing and fading over time.…”
Section: Introductionmentioning
confidence: 99%